Perencanaan Penataan Tanaman sebagai Sumber Pakan Lebah Trigona sp. dalam Sistem Agroforestri Pekarangan Berbasis Apikultur - Dea Ekaputri Andraini; Herawaty; Anugrahandini Nasir (Jurnal Galung Tropika, 2025)
Apiculture-based agroforestry is a solution to increase the value of yard land. It plays an important role in mitigating environmental balance formed from the harmonious interaction between biotic and abiotic elements in the natural environment. Gantarang Village, Sinjai Tengah District, Sinjai Regency, South Sulawesi, has natural wealth in the form of vegetation diversity that has the potential to be developed as an apiculture location. This study aimed to design apiculture-based agroforestry planning in residents' yards in Gantarang Village. Data were collected using observation techniques and made into a gold landscape design stage scheme, which included five stages: preparation, inventory, analysis, synthesis, and planning. The research stages include formulating the problem, determining the research objectives, and determining the location and boundaries of the site. Information was obtained through physical and biophysical data and secondary data from the literature. The next stage is analysis and synthesis, which was developed as a landscape planning concept. The analysis results of the synthesis of existing vegetation were maintained with the addition of vegetation maximized in empty areas so that the vegetation flowers quickly. The landscape planning applied is the ecological design concept or architectural ecology that considers the balance of nature with the artificial environment to create a habitat for Trigona sp. bees.